2021
DOI: 10.3390/soc11030076
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Roles and Consequent Decision-Making Processes of High-Level Strength and Conditioning Coaches

Abstract: Research into sports coaches has identified the valuable role they play concerning social support provided to athletes together with their contribution to social and cultural interactions within both the participation and performance domains. The purpose of the present study was to qualitatively extract and examine the knowledge and on-task cognitions of high-level coaches (HLCs) within strength and conditioning (S and C). Applied cognitive task analysis (ACTA) was used to examine ten HLCs, each purposefully s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…The richness of responses permits other SCCs to engage in the findings and recognise the concepts and examples discussed in relation to their own experiences (Smith, 2018;Smith & McGannon, 2018). The topic satisfies the criteria of being relevant, timely and significant by extending on recent investigations into the decision-making process of SCCs (Downes & Collins, 2021a;Downes & Collins, 2021b) and advocating the use of constructivist approaches within S & C development (Szedlak et al, 2021;Gearity et al, 2021). Examination of the findings should provide stimulus for coach development strategies within S & C.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The richness of responses permits other SCCs to engage in the findings and recognise the concepts and examples discussed in relation to their own experiences (Smith, 2018;Smith & McGannon, 2018). The topic satisfies the criteria of being relevant, timely and significant by extending on recent investigations into the decision-making process of SCCs (Downes & Collins, 2021a;Downes & Collins, 2021b) and advocating the use of constructivist approaches within S & C development (Szedlak et al, 2021;Gearity et al, 2021). Examination of the findings should provide stimulus for coach development strategies within S & C.…”
Section: Discussionmentioning
confidence: 95%
“…The present study sought to establish the level of agreement and disagreement Earlier research identified the significant influence that planning was deemed to have on coaching performances (Gallimore & Tharp, 2004). Previously Szed- Recently it has been reported that HLCs include information about athletes on a personal level within their decision-making processes (Downes & Collins, 2021a), while Szedlak et al (2015) reported that athletes perceive more effective SCCs to build relationships through developing trust, demonstrating high approachability, and displaying a sense of humour. We recommend that, in seeking to develop effective communication skills among SCCs, future learning strategies should be authentic and ideally situated in S & C environments to support the testing and refinement of communication skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations